Political capitalism: The interaction between income inequality, economic freedom and democracy - Tim Krieger; Daniel Meierrieks (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2015)
In this contribution we study the relationship between income inequality and economic freedom for a panel of 100 countries for the 1971-2010 period. From a panel causality study we find that income inequality has a negative causal effect on economic freedom, while causation does not run in the opposite direction. We argue that the negative effect of inequality on economic liberty is due to the elite's political power stemming from its disproportionate control over a country's economic resources. The elite uses this power to curtail economic freedom to defend its economic interests by discouraging innovation, competition and protecting its rents. Running a series of dynamic panel estimations, we show that the negative effect of income inequality on economic freedom is robust to different sets of controls and estimation techniques. Finally, we show that the dynamics of the inequality-freedom nexus are to some extent conditional upon a country's political regime. When inequality is low, democracies enjoy comparatively higher levels of economic liberty, in line with the interests of a large middle-class. By contrast, economic freedom is lower in democracies (compared to strongly autocratic regimes with the same income distribution) when inequality is high. We argue that the latter finding corresponds to a system of political capitalism or captured democracy, where a powerful economic elite cooperates with politicians and bureaucrats for their mutual benefit.
Keywords: D31; D72; 330; income inequality; economic freedom; democratic institutions; political capitalism; middle-class; captured democracy